Identification of Materials in Fragments of Large-Sized Objects in Containers by the Dual-Energy Method; Russian Journal of Nondestructive Testing; Vol. 55, iss. 9 - Osipov S. P. Sergey Pavlovich; Usachev E. Yu. Evgeny Yurjevich; Chakhlov S. V. Sergey Vladimirovich; Shchetinkin S. A. Sergey Aleksandrovich; Song S.; Zhang G. Gaolong; Batranin A. V. Andrey Viktorovich; Osipov O. S. Oleg Sergeevich (2019, 2019)
Title screen